Association between serum level of vitamin D and lipid profiles in type 2 diabetic patients in Iran - Saedisomeolia, Ahmad (BioMed Central, 2014)
BACKGROUND: It is suggested that vitamin D deficiency is associated with cardiovascular disease (CVD) via its effect on lipid profiles. The objective of this study was to determine the association between fasting serum levels of 25(OH) D and lipid profiles in patients with type 2 diabetes. METHODS: This cross-sectional study was conducted on 108 type 2 diabetics. Patients were selected randomly among members of the Iranian Diabetes Association according to study criteria. Fasting concentration of 25(OH) D, calcium, phosphorus, parathyroid hormone (PTH) and lipid profiles (including triglyceride (TG), high-density lipoprotein (HDL), low-density lipoprotein (LDL), and total cholesterol) were measured. RESULTS: The mean serum levels of 25-hydroxyvitamin D (25(OH) D) and PTH were 53.41 ± 33.25 nmol/l and 40.24 ± 18.24 pmol/l, respectively, in type 2 diabetic patients. Prevalence of vitamin D deficiency was 58.34% and vitamin D sufficiency and insufficiency combined was 41.66%. Although in diabetic patients with vitamin D deficiency, serum levels of total cholesterol, TG, and LDL were higher and HDL was lower compared to patients with vitamin D sufficiency, this association was statistically significant only for serum level of TG (145.91 ± 79.00 vs. 122.95 ± 55.82 mg/dl). CONCLUSIONS: The results of present study show that serum concentrations of 25(OH) D were inversely associated with TG. More interventional studies are needed to confirm the relationship between serum concentration of vitamin D and lipid profile in patients with type 2 diabetes.